Case report: Eisenmenger syndrome in a dog with ventricular septal defect: long term management and complications - Bruno, Barbara; Savarino, Paolo; Bussadori, Claudio; Degiovanni, Andrea; Lardone, Elena; Bertero, Alessia; Tarducci, Alberto (Frontiers in Veterinary Science, 2024)
A 9-month-old female Jack Russell Terrier was referred because of two episodes of suspected syncope. Echocardiography revealed a large, isolated mid-muscular ventricular septal defect (7 mm) with bidirectional shunting. A diagnosis of Eisenmenger syndrome and erythrocytosis (68.5% of hematocrit) was made and sildenafil therapy (0.5 mg/Kg twice daily) was initiated. Regular follow-up examinations were performed and Sildenafil therapy was gradually increased based on changes in clinical signs, packed cell volume and heart rate. The dog's clinical conditions have been stable without the need of phlebotomy for 4 years and 6 months, until April 2021 (month 74) (about 7 years of survival) when the dog had 80% of hematocrit and signs of hyperviscosity syndrome. The dosage of administered sildenafil reached gradually 6 mg/Kg DIE (2 mg/Kg three times a daily) in June 2022. Lastly, in November 2023 a closed pyometra was diagnosed and the dog was hospitalized and operated. The major concerns in the peri-operative period were hypotension and the profound hypoxemia, but the dog was discharged and recovered normal activity in approximately 11 days. This report describes the long-term management with sildenafil citrate of Eisenmenger syndrome secondary to a muscular ventricular septal defect with right-to-left shunting in a dog. Sildenafil therapy was always well tolerated with no side effects reported, even at higher dosage and drastically reduced the need for phlebotomy.